Extensional Flow and Relaxation of Semi‐dilute Solutions of Schizophyllan. Issue 9 (18th February 2013) - De Dier, Raf; Mathues, Wouter; Clasen, Christian
Abstract Capillary thinning experiments of semi‐dilute solutions of schizophyllan in water and DMSO are performed to determine the relaxation behavior in extensional flows as experienced, for example, in the flow through porous media in enhanced oil recovery. The extensional relaxation time λE is found to scale with concentration following a dissimilar power‐law dependency for the two solvents, λE ∝ c1.52 in water and λE ∝ c0.90 in DMSO. It is shown that the extensional flow fields are strong enough to break, and prevent the rebuilding of, intermolecular structures, due to hydrogen bonding that was observed to alter the viscoelastic response in shearing flows of aqueous schizophyllan solutions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>